Pemahaman Masyarakat Dan Perkembangan Kecerdasan Anak; Studi Murid Sekolah Dasar Di Kecamatan Garum Kabupaten Blitar - Riyadus Sholichin; Wasito (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
This research is framed in a big topic, namely programs, management and school facilities that are of interest to the people of Garum Sub-district, Blitar Regency. Evidently, these topics have an impact on society on how to develop children's intelligence. The community will choose a particular school based on their understanding of children's learning. This also happened in elementary schools in Garum Subdistrict, Blitar District. The problems raised in this study include questions about the understanding of the people of Garum District in Blitar Regency in choosing schools for their children and the impact of the understanding of the people of Garum District in Blitar Regency on educational institutions. The type of research approach is qualitative-descriptive. In this research, data is collected, then narrated according to the perspective of community development theory. The results of this study Garum District Community Blitar District understands that education is an important means of developing children's intelligence. For this reason, they choose schools with criteria that have the best facilities. This view is the basis for schools to improve themselves into public service institutions.